The Impact Of Mobile Phone Ownership On Farmers' Income: Evidence From Microdata In Indonesia - Fazaalloh, Al Muizzuddin; Prestianawati, Silvi Asna; Athoillah, Moh. (Universitas Pendidikan Ganesha, 2024)
Farmers in Indonesia play a crucial role in providing staple foods for the community. However, the welfare of farmers remains an unresolved issue to date. With the advancement of technology, collaboration between agricultural activities and the utilization of technology such as mobile phones should be possible, which can increase farmers' income. This study aims to analyze how mobile phone ownership among farmers can improve the welfare of farmers in Indonesia. Using microdata sourced from the World Bank's Global Financial Inclusion Index, this research employs Ordered Logistic Regression to analyze the data. The results of the data analysis indicate a significant tendency of variables such as gender, age, farmers' residential location, and savings behavior towards increasing farmers' income associated with farmers' mobile phone ownership. With the significance generated from these variables, this study can serve as a basis for agricultural stakeholders and policymakers to determine more beneficial agricultural strategies and strengthen policies that can improve farmers' welfare in the current digital era.